The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1155/2014/439818
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Road Traffic Injury and Associated Factors among Patients Visiting the Emergency Department of Tikur Anbessa Specialized Teaching Hospital, Addis Ababa, Ethiopia

Abstract: Background. Road traffic injuries are a major public health issue. The problem is increasing in Africa. Objective. To assess the incidence of road traffic injury and associated factors among patients visiting the emergency department of Tikur Anbessa Specialized Teaching Hospital, Addis Ababa, Ethiopia. Methods. Institutional based cross-sectional study design was conducted. A total of 356 systematically selected study subjects were included in the study. Bivariate and multivariate logistic regressions were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 7 publications
10
24
0
Order By: Relevance
“…The analysis of hypothesis 5 showed an existence of positive statistical influence of family size on roadsafety practice of taxi drivers in Uyo metropolis. The finding agreed with the previous studies of Adisa (2010) and Tiruneh et al (2014) who reported positive association of family size with road-safety practice. These authors explained that drivers with many children or more number of persons to provide for in their families are not always able to observe and adhere to ideal road-safety practices.…”
Section: Discussion Of Findingssupporting
confidence: 93%
“…The analysis of hypothesis 5 showed an existence of positive statistical influence of family size on roadsafety practice of taxi drivers in Uyo metropolis. The finding agreed with the previous studies of Adisa (2010) and Tiruneh et al (2014) who reported positive association of family size with road-safety practice. These authors explained that drivers with many children or more number of persons to provide for in their families are not always able to observe and adhere to ideal road-safety practices.…”
Section: Discussion Of Findingssupporting
confidence: 93%
“…The odd of road traffic injury is more than 3 times AOR = 3.05, 95% CI (1.20-7.69)higher for individual ofbelow 15 years old as compared to individual above 45 years old. This study result was consistent with finding Arbaminch General Hospital, EDHS 2016 secondary data analysis, Dicholora Hospital and Tekur Anbessa Referral Hospital (8,(12)(13)(14). It was also consistent with previous study conducted in Wolaita Zone in similar study area (7).…”
Section: Discussionsupporting
confidence: 92%
“…A qualitative study done in central Ethiopia indicated that economic problems, pedestrian ignorance and the current mismatch of vehicle eet and existing road conditions were the major factors for RTI (9). Previous studies indicated that poor road conditions were responsible for Road tra c injury (10).. A study done in Addis Ababa Ethiopia, drivers (35%) were the most vulnerable group of road tra c injury (11). Motorcycle injury was the highest as compared to other vehicles.…”
Section: Introductionmentioning
confidence: 99%